EDU708 : Qualitative research methods and analysis / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
This course introduces students to fundamental principles of qualitative educational research and prepares them in the skills, techniques and knowledge necessary to undertake research using this approach. Among the research designs that will be discussed are phenomenology, ethnography, grounded theory and case study. Students will gain practical experience in analysis, interpretation and writing based on field data, and learns about ethical framework of conducting qualitative research. Students will also learn about data analyses such as content analysis and narrative analysis. The assignment will expose students to practical experience in qualitative research in use by carrying out interviews and observations, in project relevant to domains of students’ interest.